ANALYSIS OF NEGARA RIVER SEDIMENTATION AND PREDICTION OF DAMAGE ON ANDI TAJANG BRIDGE IN HULU SUNGAI SELATAN REGENCY - Andrean R. Juanizar; M. Azhari Noor; Nilna Amal (CERUCUK, 2017)
Sediments can lead to continuous agradation and degradation that potentially alters river morphology. On the other hand, scouring occurs as a consequence of contraction due to the existence of a bridge. Contraction will make the flow form a hole under the pillar. Decreasing pillars due to scouring may endanger the overall structure of the bridge.The data used in the calculation of sediment volume is river discharge data, soil samples, and geometry of Negara River. The data were then fed into HEC-RAS 4.1.0, using four formulas: Laursen, Engelund-Hansen, Meyer Peter Muller, and Toffaleti, the calculations were then performed by HEC-RAS 4.1.0 and then analyzed. The analysis was done by using three months simulation time. While the technical data of Andi Tajang Bridge is modeled on HEC-RAS 4.1.0, and then calculates scouring by considering scouring due to contraction and pillar impact. The debit used in the calculation of the scouring of the bridge is the discharge design with 50, 100, 500, and 1000 Years reinstall.The result of research is the maximum average capacity of Negara River that is 374,214 ton/day, sediment discharge and sediment concentration are 35,347 ton/day and 6,668 mg / l. The biggest scour on Andi Tajang Bridge occurred at the discharge of 267,4116 m3 / d (re-time 1000 years) that is 2.98 m. Based on the results of the study, the sediment discharges occurring in the Negara River are of great value in some parts, so that sediment control is necessary. In addition, to prevent damage to the bridge structure due to scouring, it is necessary to make protection on the structure under the Andi Tajang Bridge. Keywords: sediment, scour, bridge, Negara River, Andi Tajang Bridge, HEC-RAS 4.1.0